Determinação de vanádio em águas usando a técnica de difusão em filmes finos por gradientes de concentração - Luko, Karen Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Diffusion Gradients in Thin Films technique (DGT) allows the in situ quantitative evaluation of the concentration of labile metals by deploying the device in an aquatic system. DGT can be used for different metals, but some adjustments are required, especially in relation to the binding layer to be used. In this study, Amberlite IRA 410 resin was evaluated as the binding layer for vanadium sampling by DGT in natural waters, which was then determined by inductively coupled plasma mass spectrometry. 1.5% agarose (0.08 cm) was used as the diffusive layer. By using the developed device, deployments were carried out at varying times (4 to 72 h). The experiment was conducted using a V-stock solution (V) and keeping some conditions stable as T=23.5 ± 0.5 ° C, ionic strength 0.03 mol L-1 and pH=5.5. It was also evaluated the effect of ionic strength (0.0003 to 1 mol L-1) and pH (3, 5, 7 and 9) on the retention of the analyte. Tests (solid phase extraction) aiming to evaluate discs exchange capacity showed a value of 40.8 μg V-1 g resin. An elution factor of 0.86 ± 0.05 was obtained. Immersion curve was characterized by excellent linear correlation (R2 = 0.9964) and a significant retention of V by the binding layer (slope> 0.0016 ng s-1). Diffusion coefficient of 7.13 ± 0.3 10-6 cm2 s-1 was obtained in agreement with the expected value (6.66 10-6 cm2 s- 1) suggesting that the developed binding agent is effective. The V uptake was not significantly affected for solutions with ionic strength up to 0.3 mol L-1, and it was efficient for the entire studied pH range. Furthermore, the technique provided a Cl- interference reduction in the V determination by ICP-MS, comparing the values obtained from this technique and the values obtained by direct measurement of the concentration of the solution. Tests carried out to identify other possible interfering ions showed no significant interfering influences on the retention of the analyte. Tests on...

A técnica difusão em filmes finos por gradientes de concentração (DGT) permite avaliar in situ quantitativamente a concentração lábil dos metais por meio da imersão de um dispositivo no sistema aquático. A DGT pode ser utilizada para diferentes metais, porém esta flexibilidade depende de adaptações, principalmente em relação ao agente ligante a ser utilizado. Neste estudo, foi avaliada a resina Amberlite IRA 410 como agente ligante na DGT para a amostragem de vanádio em águas naturais, seguida da determinação por espectrometria de massas com plasma acoplado indutivamente. Agarose 1,5% (0,08 cm) foi utilizada como camada difusiva. Usando o dispositivo desenvolvido foram realizadas imersões em períodos variados (4 a 72 h). O experimento foi conduzido a 23,5±0,5 o C utilizando uma soluçãoestoque de V (V) (força iônica 0,03 mol L-1 e pH 5,5). Também foi avaliado o efeito da força iônica (0,0003 - 1 mol L-1) e pH (3, 5, 7 e 9) na retenção do analito. Testes (extração em fase sólida) com os discos mostraram capacidade de troca de 40,8 μg V g de resina-1. Foi obtido fator de eluição de 0,86 ± 0,05. A curva de imersão foi caracterizada por excelente correlação linear (R2 = 0,9964) e retenção significativa do V no ligante (coeficiente angular > 0,0016 ng s-1). O coeficiente de difusão obtido (7,13 ± 0,3 10-6 cm2 s-1) foi concordante com o valor esperado (6,66 10-6 cm2 s-1) sugerindo que o agente ligante desenvolvido foi efetivo. A retenção de V só foi significantemente afetada para soluções com força iônica a partir de 0,3 mol L-1, e foi eficiente para toda faixa de pH estudada. Ainda, a técnica propiciou redução na interferência do Cl- na determinação de V por ICP-MS, quando comparados os valores obtidos a partir desta técnica e os valores obtidos pela medida direta da concentração da solução. Os demais interferentes estudados não apresentaram influência significativa na retenção do analito...
Keywords: Geochemistry; Geoquimica; Vanadio; Filmes finos; Gradiente de concentração